Pengaruh Efektifitas Pembiayaan Murabahah Terhadap Tingkat Pendapatan Nasabah - Nuni Oktaviani (Khulasah : Islamic Studies Journal, 2019)
Murabahah financing is financing with a sale and purchase agreement in a financial institution shown to the seller and buyer. The selling price is the purchase price plus the profit. The financial institution must state the actual price and state the profit determined according to the agreed percentage. Payment can be made by paying fixed installments according to the agreed amount until the specified time period. The main problem in this research is: "Murabahah financing distributed to large customers, but why is the customer's income level still low?" "Based on the existing problems, the researchers conducted research with the title "The Effect of Murabahah Financing Effectiveness on Customer Income Levels" (Case study at BMT AL-Falah Sumber Cirebon Regency). The discussion in this research uses quantitative descriptive methods. The descriptive meaning is: "Research is intended to investigate circumstances, conditions, situations, events, activities and other things, the results of which are presented in the form of a research report." Population is a generalized area consisting of: objects/subjects that have certain qualities and characteristics determined by the researcher to be studied and conclusions drawn." The population used in this research is customers who use murabahah contracts, namely 560 customers. To determine the sample, the researcher selected 10% of the existing population. Thus, the number of samples in this study is: 560 x 0.10 = 56, or the sample in this study is 56 people. Based on the results of the research conducted, conclusions can be drawn. The effectiveness of murabahah financing has a significant influence on the level of customer income in Baitul Maal wa Tamwil Al-Falah Sumber Cirebon Regency. It is proven from the calculation results of t_count > t_table, namely 6,625 > 2,000. The results of the coefficient of determination test show that the level of customer income can be explained by the effectiveness of murabahah financing by 44.8%, while the remaining 55.2% is influenced by other variables not included in this research.